2017
DOI: 10.1002/jca.21544
|View full text |Cite
|
Sign up to set email alerts
|

Membrane therapeutic plasma exchange with and without heparin anticoagulation

Abstract: Our findings indicate that TPE procedures can be conducted safely with UH and, when necessary, without anticoagulation. The use of LMWH was associated with more complications when compared with use of UH and to TPE done without anticoagulation. Further studies are necessary to study its use during TPE procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
1
20
0
3
Order By: Relevance
“…Thus, in a population of critically ill patients undergoing TPE for various indications, the absence of anticoagulation didn't lead to an increased risk of filter clotting[41]. Nevertheless, this study might have been underpowered as larger cohort reported a three-fold increase in the frequency of such complication when only saline flushing was used as compared with unfractionated heparin[42]. However, membrane filtration plasmapheresis without anticoagulation for the first sessions of TPE should be an option to consider in some patients at high risk of bleeding or already experiencing such complication, especially when regional citrate anticoagulation is unavailable and/or contraindicated.…”
mentioning
confidence: 92%
“…Thus, in a population of critically ill patients undergoing TPE for various indications, the absence of anticoagulation didn't lead to an increased risk of filter clotting[41]. Nevertheless, this study might have been underpowered as larger cohort reported a three-fold increase in the frequency of such complication when only saline flushing was used as compared with unfractionated heparin[42]. However, membrane filtration plasmapheresis without anticoagulation for the first sessions of TPE should be an option to consider in some patients at high risk of bleeding or already experiencing such complication, especially when regional citrate anticoagulation is unavailable and/or contraindicated.…”
mentioning
confidence: 92%
“…In a study of 85 patients undergoing 225 TPE procedures, compared to citrate, heparin was associated with more bleeding complications (11.8% vs 0%) 20 . In another study of 1034 patients undergoing 9611 TPE procedures, bleeding complications were reported in 13 procedures, of which 85% (11/13) occurred with unfractionated heparin or low‐molecular‐weight heparin 22 . In this study, bleeding complications were noted in 2 procedures without circuit anticoagulation 22 .…”
Section: Effects Of the Tpe Proceduresmentioning
confidence: 48%
“…The most common circuit anticoagulants for TPE are citrate and unfractionated heparin 20,21 . Citrate is preferred in the majority of procedures because of its low cost, safety, and effectiveness 20,22 . Citrate, an effective regional anticoagulant that acts by calcium chelation, is rapidly neutralized as soon it returns to and is mixed with systemic blood flow 20,22 .…”
Section: Effects Of the Tpe Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…К примеру, когда задействуется мембранная технология ОПП, стандартный протокол включает начальную нагрузочную дозу 1000 Ед нефракционированного гепарина (НФГ) с последующей его инфузией в ходе всей процедуры со скоростью 500 Ед/ч. И хотя общее число геморрагических осложнений ОПП составляет всего 0,1-0,26% [46,59], такой режим при ДАК повышает геморрагический риск, требуя соответствующей корректировки в индивидуальном порядке в процессе каждой конкретной процедуры (с описанием вариаций инфузии гепарина при высоком риске кровотечений можно познакомиться в работе B. Puppe и соавт. [60]).…”
Section: обзорunclassified